Analisis Spektroskopi Ftir Untuk Karakterisasi Kimia Fisik Fluida Mata Air Panas Di Kawasan Wisata Hutan Pinus Tomohon Sulawesi Utara - Ridel Raturandang; Donny Royke Wenas; Satyano Mongan; Cyrke Bujung (Jurnal FisTa : Fisika dan Terapannya, 2022)
Geothermal is one of the alternative energy sources that are classified as new and renewable (new and renewable). This is because geothermal energy sources are still relatively new and are said to be renewable because production waste in the form of water is re-injected and produces a recycle process that allows sustainability. The process of exploration, exploitation and production does not produce toxic gas emissions. In terms of prospects, geothermal itself is a promising energy in the future because the source is heat from within the earth that will never run out. One of the areas in North Sulawesi that has the potential for geothermal project development is located in the Tomohon area, North Sulawesi Province. Based on the preliminary survey that has been carried out, at this location found manifestations in the form of hot springs located in the Pine Forest. The purpose of this study was to determine the type of fluid and functional groups of molecules manifesting hot springs in the Tomohon pine forest tourism area. Analysis of the ion content in the fluid using spectrophotometer characterization, and analysis of molecular functional groups using FTIR (Fourier Transform Infra Red) spectroscopy. The results showed that the type of fluid manifestation of the hot springs in the Tomohon Pine Forest Tourism Area has the type of bicarbonate (HCO3). Analysis of functional groups of fluid molecules in the manifestation of hot springs in the Tomohon Pine Forest Tourism Area has functional groups C=O, C≡C and O-H.